2019
DOI: 10.1093/jscr/rjz004
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel intussusception and concurrent sigmoid polyp with malignant transformation in Peutz–Jeghers syndrome

Abstract: Peutz–Jeghers syndrome (PJS) is an autosomal dominant condition characterized by the association of gastrointestinal polyposis, mucocutaneous pigmentation and cancer predisposition McGarrity, Amos, Baker (Peutz–Jeghers Syndrome, GeneReviews(R), National Center of Biotechnology Information.). Intussusception and malignant polyps are not rare complications of PJS, where the lifetime risk of intussusception is 48% and the possibility of developing any cancer by age 65 years is 37% Kopacova, Tacheci, Rejchrt, Bure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Color Doppler US showed central blood flow in the pedicles and rich blood flow signals radiating from the center to the edge of the nodules. Polyps of Peutz-Jeghers syndrome, commonly found in the small intestine are also described as hamartomas [38]. US images showed that the polyp was a lobulated nodule with an alternative distribution of hyperechoic and hypoechoic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler US showed central blood flow in the pedicles and rich blood flow signals radiating from the center to the edge of the nodules. Polyps of Peutz-Jeghers syndrome, commonly found in the small intestine are also described as hamartomas [38]. US images showed that the polyp was a lobulated nodule with an alternative distribution of hyperechoic and hypoechoic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The hamartomas are located in the small intestine in >90% of patients, predominantly in the jejunum ( 3 ). Even in the early childhood, the hamartomas may induce complications including bleeding, abdominal pain, anemia, and intussusception ( 4 ). In this study, we took PJS pedigree as the research object, the first symptom of the proband was intussusception.…”
Section: Introductionmentioning
confidence: 99%
“…12 No. 01 nasal passages, bronchial tree, lung, breast, kidney, ureter, pancreatic, gallbladder, uterine, ovarian and testicular tumors 5,6. Although the hamartomatous polyps are known with low malignant potential, individuals with this disease are at elevated risk of acquiring malignancies.3 Overall lifetime GI cancer risks of 55-85% and the reported lifetime risk for any cancer varied according to the literature between 37% and 93% at the age of 60-70 years.…”
mentioning
confidence: 99%